EMPOWERING RURAL COMMUNITIES: ANALYZING THE IMPACT OF THE BACK TO VILLAGE PROGRAM IN JAMMU AND KASHMIR - Ramparshad Singh; Dr. Nand Kishore Somani (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
This research paper delves into the effectiveness and impact of the Back to Village (B2V) program initiated by the Government of Jammu and Kashmir in the Union Territory of J&K. The B2V program aims to promote grassroots democracy and expedite rural development by facilitating direct interaction between government officials and local communities. The paper examines various aspects of the program, including community engagement, implementation challenges, and the effects on rural infrastructure, education, healthcare, and employment. Using diverse methodologies of data collection including field visits and interviews, the paper comprehensively analyzes community feedback and participation levels. While there have been significant improvements in public service delivery and development, certain challenges related to implementation and sustainability persist. Policy implications and recommendations for enhancing the program's effectiveness are discussed, along with suggestions for future research. The study underscores the importance of community involvement in rural governance and provides valuable insights for policymakers aiming to improve rural development strategies in Jammu and Kashmir.